2007
DOI: 10.1038/sj.cgt.7701091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of RNA oligonucleotide targeting Foxo-1 on muscle growth in normal and cancer cachexia mice

Abstract: Foxo-1, a member of the Foxo forkhead type transcription factors, is markedly upregulated in skeletal muscle in energy-deprived states such as fasting, cancer and severe diabetes. In this study, we target the Foxo-1 mRNA in a mouse skeletal myoblast cell line C2C12 and in vivo models of normal and cancer cachexia mice by a Foxo-1 specific RNA oligonucleotide. Our results demonstrate that the RNA oligonucleotide can reduce the expression of Foxo-1 in cells and in normal and cachectic mice, leading to an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 16 publications
(16 reference statements)
6
55
0
1
Order By: Relevance
“…Therefore, we suggest that myostatin may not be required to induce muscle wasting during undernutrition in sheep. In contrast, others have reported that the expression of myostatin decreased in animal models of cancer cachexia [40], sarcopenia [41], denervation-induced muscle wasting [42], or showed no change in unloading-induced skeletal muscle atrophy [43,44]. Finally, transgenic postnatal expression of myostatin reduced muscle mass by 20% in males only and had no effect on females [45].…”
Section: Discussionmentioning
confidence: 53%
“…Therefore, we suggest that myostatin may not be required to induce muscle wasting during undernutrition in sheep. In contrast, others have reported that the expression of myostatin decreased in animal models of cancer cachexia [40], sarcopenia [41], denervation-induced muscle wasting [42], or showed no change in unloading-induced skeletal muscle atrophy [43,44]. Finally, transgenic postnatal expression of myostatin reduced muscle mass by 20% in males only and had no effect on females [45].…”
Section: Discussionmentioning
confidence: 53%
“…In our study, Foxo1, Foxo3, and Foxo-4 were upregulated in 85As2-induced cachectic rats, and their increased expression was thought to be associated with the increased expression of atrogin-1 and MuRF-1. Notably, the elevation of Foxo1 levels was prominent, and its blockade suppressed cachectic muscle atrophy (36). Expression of the protein synthetic factor IGF-I has been reported to decrease in cancer cachexia models (16).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mice specifically overexpressing Foxo1 in skeletal muscle were found to weigh less than wild-type control mice and had a reduced skeletal muscle mass, with loss of both type I and type II fibers, and the muscle was paler in color (125). There was increased expression of atrogin 1, but not MuRF1, together with an increased expression of the lysosomal proteinase cathepsin L. Downregulation of Foxo-1 expression using a specific RNA oligonucleotide led to an increase in skeletal muscle mass in cachetic mice, with an increased level of MyoD and decreased levels of the muscle regulator myostatin (150). Also constitutively active Foxo 3 acts on the atrogin-1 promoter increasing transcription and causing massive atrophy of myotubes and muscle fibers (233).…”
Section: B Glucocorticoidsmentioning
confidence: 96%